Short-Term Fasting and Ingestion of Caloric Drinks Affect Heartbeat-Evoked Potentials and Autonomic Nervous System Activity in Males - Flasbeck, Vera; Bamberg, Christoph; Brüne, Martin (Frontiers in Neuroscience, 2021)
Central nervous systems receive and process information from the internal and external environment to maintain homeostasis. This includes interoceptive awareness of the organism’s nutritional state. Whenever food supply is required, feelings of hunger initiate the search for and the consumption of appropriate amounts of nutrients. How this is physiologically regulated in humans has been subjected to research into interoceptive awareness of body states during fasting and food consumption. However, there is no research on the distinct effects of carbohydrate or protein intake on interoception. Therefore, we aimed to investigate the impact of fasting and consumption of standardized carbohydrate and protein shakes on interoception in a repeated-measures cross-over design in a sample of thirty-seven healthy, normal weight males. As a physiological correlate of interoception, we measured heartbeat-evoked potentials (HEP), which are suggested to reflect the cortical representation of cardiac signals, during eight-minutes resting state EEG-recordings. After a 16-hour fasting period, the HEP amplitudes were lower over right central and parietal electrodes and increased after ingestion of the nutritional shake. Exploratory analyses indicated that the difference between fasting and satiety was more prominent at carbohydrate compared protein testing days. Correlation analyses with heart rate variability suggested that high cardiac sympathetic activity is related to lower HEP amplitudes. Furthermore, cardiac sympathetic activity and stress indices decreased from before to after the intervention, whereas heart rate variability increased. Together, this study shows for the first time that fasting and the intake of a nutritional shake affects cardiac measures of autonomic nervous system functioning and the neural correlates of cardiac interoception. These findings could be relevant for diets and psychosomatic disorders, including eating disorders.